Strength Analysis of Frame Structure Loading in Planning Using Solidworks Static Simulation Study - R M Bisono; N Hafidhoh; A T A Salim (Biomedical and Mechanical Engineering Journal (BIOMEJ), 2021)
The main focus of this research is to design the frame of the various chips chopper machine that is sturdy according to the needs and has a long life. The design and simulation were carried out using the Solidworks 2020 software. The material used to make the frame structure was ASTM A36 Steel with a density of 7850 kg/m3. The mass of the chopper machine frame that has been made is 6,383 kg. By giving two kinds of loading F1 and F2 of 18.718 N and 29.4 N, the resultant displacement for F1 and F2 is 0.1088 mm and 0.0124 mm, respectively, and the maximum Von Mises Stress value is 9.846 x 106 N/m2 and 1.330 x 106 N/m2, respectively. Based on these results, according to the theoretical calculation of maximum shear stress, the maximum Von Mises stress value caused by external forces for both is very much smaller than the Yield Strength Material value (2,500 x 108 ). So that this frame structure is declared safe and can be continued into the manufacturing process of various chips chopping machines according to the workload.